Cross-modal effects of illuminance and room temperature on indoor environmental perception. (December 2018) - Yang, Wonyoung; Moon, Hyeun Jun
Abstract: The cross-modal effects of illuminance and room temperature were investigated in an indoor environmental chamber with 120 university students (60 men and 60 women) aged 18–26 years. A within-subject design was employed with three independent variables: illuminance level (150, 500, and 1000 lx), room temperature (20, 25, and 30 °C), and gender. Thermal (coldness and hotness) and visual (brightness and relaxation) semantic attributes were assessed using an 11-point numeric scale. The illuminance level of the ambient lighting system did not affect the coldness or hotness. However, the brightness and relaxation were affected by the illuminance and room temperature. The effect sizes of room temperature on both brightness and relaxation were relatively marginal in the test configurations, although the effects of room temperature were significant on the brightness and relaxation according to ANOVA. The cross-modal interactions were asymmetric between the illuminance and room temperature in the indoor environmental settings. The highest visual relaxation of eyes was at 25 °C and 500 lx. No gender differences were observed for brightness and relaxation. Highlights: Room temperature (20–30°C) affected spatial brightness and visual relaxation with a small effect size. Visual relaxation as a semantic attribute for illuminance perception was affected by both illuminance and temperature. Illuminance had a dominant effect on brightness as a semantic attribute for illuminance sensation. Indoor illuminance levels from 150 lx to 1000 lx did not affect thermal sensation. Gender differences in terms of brightness and relaxation were not found.